1994
DOI: 10.1103/physrevb.49.11409
|View full text |Cite
|
Sign up to set email alerts
|

Energy partition inC60-diamond-(111)-surface collisions: A molecular-dynamics simulation

Abstract: Collisions of Cso with hydrogen-terminated diamond-(111) surfaces were studied by moleculardynamics simulations based on a semiempirical density-functional approach. The dominating factor determining the energy partition in the Cso-diamond-(111)-surface collision at constant impact energy is the orientation of the molecules relative to the initial impact points on the surface. In agreement with the experimental results using velocity-selective time-of-Sight mass spectroscopy the center-of-mass kinetic energies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0

Year Published

1994
1994
2001
2001

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 14 publications
2
19
0
Order By: Relevance
“…The MD based theoretical estimations for the translational to vibration conversion efficiency for 60-250 eV collisions of C 60 ϩ ions with hydrogen terminated diamond ͑111͒ surface vary in the range of 15%-40%. Mowrey et al 15 predict a value of 25%, Gally and Mauri 20 predict a value of 14%, while Blaudeck et al 21 predict up to 40% efficiency. It should be added that both Mowrey et al 15 and Gally and Mauri 20 predict relatively large recoil kinetic energies which linearly scale with impact energy, as opposed to the extreme inelasticity, independent of impact energy, observed in the C 60 ϩ scattering experiments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The MD based theoretical estimations for the translational to vibration conversion efficiency for 60-250 eV collisions of C 60 ϩ ions with hydrogen terminated diamond ͑111͒ surface vary in the range of 15%-40%. Mowrey et al 15 predict a value of 25%, Gally and Mauri 20 predict a value of 14%, while Blaudeck et al 21 predict up to 40% efficiency. It should be added that both Mowrey et al 15 and Gally and Mauri 20 predict relatively large recoil kinetic energies which linearly scale with impact energy, as opposed to the extreme inelasticity, independent of impact energy, observed in the C 60 ϩ scattering experiments.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that recent direct measurements have shown that the apparent activation energy for C 2 ejection from neutral C 60 following a pure thermal excitation is much lower ͑ϳ4.5 eV͒. [16][17][18][19] Although three independent molecular dynamics ͑MD͒ calculations were performed, 15,20,21 there is yet no direct experimental measurement ͑based on independent calibration͒ available for the vibrational excitation efficiency in any C 60 scattering experiment. The MD based theoretical estimations for the translational to vibration conversion efficiency for 60-250 eV collisions of C 60 ϩ ions with hydrogen terminated diamond ͑111͒ surface vary in the range of 15%-40%.…”
Section: Introductionmentioning
confidence: 99%
“…In such conditions, the kinetic energy per atom is pretty close to, or even above the cohesive energy of the substrate and of the impinging molecule. This surprising effect stimulated studies of surface scattering mechanisms, both experimentally and by atomic scale computer simulations [5][6][7][8][9][10][11]. Resilience and fragmentation were measured for free molecules excited by excimer laser pulses [5], electron impacts [12,13] or via cluster-surface collision processes [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…In the current system, for undoped PBS a-C films, since the activation energy change is small it is likely that the variation observed in the range 0.2-0.3 eV is due to carrier activation from the valence band to the p-type structured defect present in the a-C network which has been reported both experimentally 30 and theoretically. 31 The conduction process in a-C will have a strong dependence on the structure of the film. This is illustrated by the fact that the conductivity at room temperature of the deposited films varies over two decades despite E a being apparently constant.…”
Section: Figmentioning
confidence: 99%